HUBUNGAN RASA TAKUT ANAK TERHADAP PERAWATAN GIGI DENGAN UMUR DAN JENIS KELAMIN PADA SISWA SEKOLAH DASAR NEGERI 3 PADANG SAMBIAN KELOD 2019 - Asep Arifin Senjaya; Ni Ketut Ratmini; Ni Made Sirat; Ida Ayu Novita Pranata sari (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Most children are not cooperative during the treatment process so that the dentist has difficulty handling the child. Research by Ida Ayu Novita Pranata Sari, at the State Elementary School (SDN) 3 Padang Sambian Kelod Denpasar in 2019 concluded that most respondents who felt the most fear was that their teeth had cavities and had to be patched at a dental clinic. The purpose of this study was to determine the relationship of children's fear of dental care with age and sex in students of SDN 3 Padang Sambian Kelod Denpasar in 2019. This type of research is cross sectional, using secondary data from the research of Ida Ayu Novita Pranata Sari. The results of the correlation test between age spearmen and the source of fear of dentists or dental nurses are sig 0.032; age by being invited to check their teeth at the dental clinic with a sig value of 0.036. In conclusion, there is a relationship between age and the source of fear for dentists or dental nurses and being invited to have their teeth examined at a dental clinic.